Role of minimal invasive surgeries in gastric neoplastic diseases; how far we have come: an experience at tertiary centre - P., Pote Maroti; Rafe, Abdul (International Surgery Journal, 2017)
Background: Minimal invasive surgery (MIS) is a means of performing major operations through small incision, often using miniaturized, high tech imaging systems, to minimize the trauma of surgical exposure without compromising the quality of the surgical procedure. Upper gastro intestinal (GI) diseases constitute majority of gastro intestinal pathologies. With improved diagnostic and screening modalities, even in fatal diseases like carcinoma stomach (Ca stomach), MIS offers not only complete treatment but also improved quality of life by decreasing morbidity and mortality. This study attempts to explain our experience with MIS being performed at our institute. Methods: This study is hospital based, non-randomized prospective study carried out in the Department of Surgery, Govt. Cancer Hospital, Aurangabad from August 2014 to December 2016. Total 30 patients were included in study. All gastric neoplastic diseases operated by minimal invasive surgeries in patients of all age groups were included. All patients were operated under general anaesthesia. Post-operative pain scoring was done according to VAS scale. All patients were kept in ICU in immediate post-operative period for 2-3 days. Then patients were shifted to general ward once patients were clinically stable. Patients were discharged according to recovery. Hospital stay was prolonged in cases having complications. Patients were followed up post operatively after 1, 3 and 6 months and assessed on basis of symptoms. Results: Maximum patients belonged to the age group of 41-60 years. Mean age of patients operated for Gastrointestinal stromal tumours (GIST) was 57.5 years and Ca Stomach was 56.6 years. Mean operative time for laparoscopic gastrojejunostomy in our study was 150 min, for laparoscopic gastrectomy with gastro jejunal anastomosis was 230 min and for benign gastric tumours including GIST was 112 min. Type of anastomosis: Among 16 anastomoses, 2 oesophago - jejunal, 7 gastro - jejunal and 7 cases of gastro - gastric anastomosis were done. Jejuno - jejunal anastomoses are not included in this series. Both the oesophago - jejunal anastomoses were done by stapler method. Conclusions: It can be concluded that, minimal invasive surgeries for gastric diseases are feasible to perform. Blood loss, post-operative analgesia and hospital stay are less in laparoscopic procedures so it decreases over all hospital cost. Early post-operative recovery, decreased post-operative morbidity and avoiding unnecessary laparotomies are some of the other advantages of MIS. So, MIS should be considered as an alternative for open procedures in gastric disorders, for betterment of patient care.